A description of rodlet cells from the alimentary canal of Anguilla anguilla and their relationship with parasitic helminths - SAYYAF DEZFULI, Bahram; CAPUANO, Silvia; M. Manera (Journal of Fish Biology, 1998)
Rodlet cells in intestinal epithelia of infected and uninfected European eels Anguilla anguilla from brackish and fresh water were studied by light and electron microscopy. Deropristis inflata (Trematoda) was found in eels from brackish water, whereas eels from fresh water were infected with Acanthocephalus clavula (Acanthocephala). In a comparison between uninfected and infected eels from brackish water, a higher number of rodlet cells was recorded in the intestinal epithelia of infected fish. Evidence is presented that rodlet cells secrete their contents in a holocrine manner into the lumen of the eel intestine. The occurrence of organelles within the mature rodlet cell was rare.